Colonial Archive Gaps and Historical Trauma: Reading Krakatau 1883 and the Geger Cilegon 1888 in Postcolonial Consciousness - Ubaidil Fithri; Ribut Basuki (Institute of Research and Community Outreach - Petra Christian University, 2026)
The 1883 Krakatoa Eruption and the 1888 Geger Cilegon represent two pivotal events in the colonial history of the Banten region. Nevertheless, within colonial historiography, these occurrences are predominantly depicted through administrative archives that prioritize geological aspects and political stability, often marginalizing local communities’ social and cultural experiences. This omission creates a gap in historical narratives that not only impairs our comprehension of the past but also influences the consciousness of postcolonial generations raised amidst distorted archival records. This article examines the role of colonial archives in fostering historical ignorance and trauma transmitted across generations. Employing a qualitative interpretive approach and the frameworks of postcolonial theory, transgenerational trauma, and the social construction of history, this article explores the interplay between archives, historical silences, and the formation of collective memory. The analysis reveals that the exclusion of local voices from colonial archives is not neutral; rather, it serves as an epistemic mechanism that perpetuates this disconnection. These findings underscore that postcolonial historical trauma is not solely inherited through direct memory but also through narrative voids and the inability of subsequent generations to access their history fully. This article contributes to cultural history and postcolonial studies by identifying archival voids as active elements that shape historical consciousness and postcolonial identity in Indonesia.